Norway : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Norway. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that Norway is in the midst of a healthy recovery from the oil downturn, supported by positive trends in oil prices and a strengthening labor market. In addition, banks remain profitable and well capitalized. However, household debt continues to increase and house prices have resumed their rise, especially in the Oslo area, after a correction during 2017. Mainland growth is projected to increase from 2 percent in 2017 to 2.5 percent in each 2018 and 2019, underpinned by solid consumption, stronger business investment and an export recovery. Petroleum investment will also pick up. As a result, output will likely start to exceed potential in 2019.